2017
DOI: 10.1055/s-0043-107243
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia and the Association with All-Cause Mortality and Cardiovascular Mortality

Abstract: Hyperprolactinemia has been suspected to increase mortality risk, but the available data are conflicting. The objective of this study was to estimate the association between hyperprolactinemia and all-cause and cardiovascular mortality among patients referred for assessment of prolactin. For this study, adults with no prio pituitary disease who underwent prolactin assessment at 3 university Hospitals in Denmark between 2001 and 2011 were included in a retrospective cohort study. A total of 3 633 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
3
15
1
Order By: Relevance
“…In line with this, males are diagnosed at an older age than females, possibly implying longer diagnostic delay and exposure to the consequences of hyperprolactinaemia and of related hypogonadism . Interestingly, a recent retrospective cohort study including approximately 373 individuals with hyperprolactinemia (irrespective of its primary aetiology) reported similar findings with our study . In this report, male hyperprolactinaemic patients had a higher IRR for cardiovascular and all‐cause mortality in contrast to female patients, in whom no difference was noted when compared to normoprolactinaemic controls .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with this, males are diagnosed at an older age than females, possibly implying longer diagnostic delay and exposure to the consequences of hyperprolactinaemia and of related hypogonadism . Interestingly, a recent retrospective cohort study including approximately 373 individuals with hyperprolactinemia (irrespective of its primary aetiology) reported similar findings with our study . In this report, male hyperprolactinaemic patients had a higher IRR for cardiovascular and all‐cause mortality in contrast to female patients, in whom no difference was noted when compared to normoprolactinaemic controls .…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a recent retrospective cohort study including approximately 373 individuals with hyperprolactinemia (irrespective of its primary aetiology) reported similar findings with our study . In this report, male hyperprolactinaemic patients had a higher IRR for cardiovascular and all‐cause mortality in contrast to female patients, in whom no difference was noted when compared to normoprolactinaemic controls . Of note, an older study of a case‐control design which explored prolactin levels in those who suffered a coronary artery event and controls did not find higher prolactin levels in the affected patients .…”
Section: Discussionsupporting
confidence: 88%
“…For example, in a population-based study, pituitary tumor-related hyperprolactinemia did not show an increased risk for diabetes, vascular disease, bone fracture, and all causes of cancer and breast cancer; however, macroadenomas, drug-induced hyperprolactinemia, and idiopathic hyperprolactinemia were associated with an increased risk of death ( 48 ). Another study showed that in men, but not in women, hyperprolactinemia would be associated with higher all-cause and cardiovascular mortality ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent large cohort studies, high prolactin levels within and above the normal physiological range have been associated with increased risk of cardiovascular mortality (1, 2, 3). It is speculated whether this association is mediated through prolactin-induced increase in cardiovascular risk factors including obesity, dyslipidemia and insulin resistance (4, 5, 6, 7, 8, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prolactin levels prospectively correlated with higher levels of low-density lipoprotein (LDL) in women, and with hypertension and incidence of diabetes in men (11). In two large cohort studies hyperprolactinemia was associated with increased incidence of cardiovascular disease and cardiovascular mortality in men only (2, 3). However, the association between prolactin and excess disease burden is not consistent: In a case–control study with 1204 cases of hyperprolactinemia, no increased morbidity or mortality was found (12), and in a large cohort, levels of prolactin did not differ between those participants who suffered from fatal or nonfatal coronary artery disease and those who did not (13).…”
Section: Introductionmentioning
confidence: 99%